ANALISIS FAKTOR KEMISKINAN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI KOTA PADANGSIDIMPUAN - Abdelina .; Lilis Saryani (Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to learn about poverty, and compare the Economy to the Human Development Index in Padangsidimpuan City simultaneously. This research is classified into research documentation or library research (Library Research). The method used in this study is a quantitative method using panel data using a fixed effect model, the steps of this study are secondary data collection obtained from the Central Statistics Agency after data analysis. Based on the results of the analysis obtained from the results of the study: partially by using the Fixed Effects Model Analysis tool produces a negative variable on the Human Development Index in Padangsidimpuan City, comparing the Economy associated with the Human Development Index in Padangsidimpuan City. While seen by simultaneous poverty and published Economics related to the Human Development Index in Padangsidimpuan City.